Reproducibility in systems biology modelling. Issue 2 (23rd February 2021) - Tiwari, Krishna; Kananathan, Sarubini; Roberts, Matthew G; Meyer, Johannes P; Sharif Shohan, Mohammad Umer; Xavier, Ashley; Maire, Matthieu; Zyoud, Ahmad; Men, Jinghao; Ng, Szeyi; Nguyen, Tung V N; Glont, Mihai; et al.
Abstract : Reproducibility of scientific results is a key element of science and credibility. The lack of reproducibility across many scientific fields has emerged as an important concern. In this piece, we assess mathematical model reproducibility and propose a scorecard for improving reproducibility in this field. Abstract : Reproducibility of scientific results is a key element of science and credibility. This piece assesses the reproducibility of mathematical models and presents an 8‐point scorecard for improving model reproducibility.